Comparison of technical and systems-based approaches to managing pesticide contamination in surface water catchments - Villamizar, Martha L.; Stoate, Chris; Biggs, Jeremy; Morris, Carol; Szczur, John; Brown, Colin D. (Journal of environmental management, 2020)
Diffuse pollution of surface waters by herbicides remains a problem despite 25 years of research into mitigation approaches. This study adopts the grassweed herbicide propyzamide as a focus to compare the efficacy of technical, field-scale, interventions with systems-based cropping solutions in a 900 ha headwater catchment on heavy clay soils. Catchment monitoring was combined with modelling of land management options using SWAT, and semi-structured discussions with farmers. Vegetated buffers are the main mitigation in the catchment at present, and these are estimated to be halving propyzamide concentrations in the headwater stream. Increasing vegetated buffers to 20 m width around all water courses would be the most effective technical intervention. Collaboration between farmers to ensure differentiated application timings would be ineffective without precise forecasting to avoid application soon before storm events. Downstream pesticide limits could only be met by restricting the area of land treated with propyzamide, requiring a switch away from oilseed rape cultivation. This restriction was not acceptable to farmers who noted the lack of enablers for coordination between landowners and the need for pesticide targets that are specific to headwater catchments. •Headwater catchments can be subject to intense pressure from single pollutants.•Existing technical, field-scale interventions halved diffuse herbicide pollution.•Systems-based solutions are most effective in reducing diffuse pollution further.•Mechanisms are required to deliver effective coordination between landowners.•Pesticide pollution targets specific to headwaters will aid negotiation with farmers.